ANALISIS PENERAPAN MANAJEMEN BUDAYA SEKOLAH TERHADAP PEMBENTUKAN KARAKTER PESERTA DIDIK MIS MIFTAHUL JANNAH BANDAR LAMPUNG - Diyan Triyanto; Tiara Farashinta; Feristina Yuliani; Muhammad Kaulan Karima (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Abstract: This study aims to examinei the implementation of school environmental culture management on the character building of students at MIS Miftahul Jannah Bandar Lampung. The research employed a qualitative approach with a descriptive type of study. Data were collected through observation, interviews, and documentation involving the principal, teachers, and students as research informants. Data analysis used the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. The results showed that the implementation of school environmental culture management was carried out through the stages of planning, implementation, and evaluation. The environmental culture programs implemented included classroom cleaning schedules, Friday clean-up activities, community service activities, and habituation of maintaining school cleanliness. The implementation of these programs had a positive impact on students’ character building, particularly in the aspects of discipline, responsibility, environmental awareness, and cooperation. The role of teachers as role models became an important factor in supporting the success of character formation through the school environmental culture. However, the study also found several obstacles, such as the inconsistency of some students and the evaluation system that had not been optimally structured. Therefore, strengthening the evaluation system and involving all school members are necessary to ensure that the implementation of environmental culture can run more effectively and sustainably. In conclusion, school environmental culture management has proven to be a relevant strategy in supporting students’ character building in the modern era. KEYWORDS School Environmental Culture Management, Character Building, Environmental Awareness, Character Education, Elementary School Students Abstrak: Penelitian ini bertujuan untuk mengkaji penerapan manajemen budaya lingkungan sekolah terhadap pembentukan karakter peserta didik di MIS Miftahul Jannah Bandar Lampung. Penelitian menggunakan pendekatan kualitatif dengan jenis deskriptif. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi yang melibatkan kepala sekolah, guru, dan peserta didik sebagai informan penelitian. Analisis data menggunakan model interaktif Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penerapan manajemen budaya lingkungan sekolah dilaksanakan dengan tahapan perencanaan, pelaksanaan, dan evaluasi. Program budaya lingkungan yang diterapkan meliputi kegiatan piket kelas, Jumat bersih, kerja bakti, dan pembiasaan menjaga kebersihan lingkungan sekolah. Implementasi program ini memberikan dampak positif terhadap pembentukan karakter peserta didik, terutama pada aspek disiplin, tanggung jawab, kepedulian lingkungan, dan kerja sama. Peran guru sebagai teladan menjadi faktor penting dalam mendukung keberhasilan pembentukan karakter melalui budaya lingkungan sekolah. Namun disisi lain, penelitian juga menemukan beberapa kendala, seperti kurangnya konsistensi sebagian peserta didik serta sistem evaluasi yang belum terstruktur secara optimal. Oleh karena itu, diperlukan penguatan evaluasi dan keterlibatan seluruh warga sekolah agar penerapan budaya lingkungan dapat berjalan lebih efektif dan berkelanjutan. Dengan demikian, manajemen budaya lingkungan sekolah terbukti menjadi strategi yang relevan dalam mendukung pembentukan karakter peserta didik di era modern. KEYWORDS Manajemen Budaya Lingkungan Sekolah, Pembentukan Karakter, Kepedulian Lingkungan, Pendidikan Karakter, Peserta Didik Sekolah Dasar